2000
DOI: 10.1139/l99-061
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tailwater depth on the dynamics of local scour

Abstract: The two-dimensional local scour occurring downstream from a submerged sluice gate for various tailwater depths was studied using a video imaging technique and a laser-Doppler anemometer. The flow field was found to be dynamic (i.e., varied with time). Previously reported equilibrium scour profiles for similar test conditions were not attained even after 96 h of laboratory testing. The scaling laws suggested in the literature were found to be unsuitable. New scaling laws are presented for the condition when a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…The reason for this is that the energy of the jet that formed the scour was dissipated by diving into the water bag that was formed when the tailwater level increased. Previous research has shown that the dynamics of local scour is dependent on the tailwater depth (for example; Balachandar et al, 2000;Mohamed and McCorquodale, 1992;Johnston, 1990;Chatterjee and Ghosh, 1980). Figure 9 shows that, for a stepped chute, the velocity at the end of the stilling basin increased proportional to the increase in cute angle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this is that the energy of the jet that formed the scour was dissipated by diving into the water bag that was formed when the tailwater level increased. Previous research has shown that the dynamics of local scour is dependent on the tailwater depth (for example; Balachandar et al, 2000;Mohamed and McCorquodale, 1992;Johnston, 1990;Chatterjee and Ghosh, 1980). Figure 9 shows that, for a stepped chute, the velocity at the end of the stilling basin increased proportional to the increase in cute angle.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Balachandar and Kells (1998) showed that the dynamics of local scour is dependent on the tailwater depth. Balachandar et al (2000) used a video imaging technique to study the effect of tailwater depth on the dynamics of local scour.…”
Section: Introductionmentioning
confidence: 99%
“…Box-whisker plot of supercritical jet slopes for boulder-bed submerged jump region and pure-bedrock unsubmerged jump region for low (Q = 0.7 m 3 s −1 ) and high (Q = 1.4 m 3 s −1 ) discharge conditions, respectively. few flume-based jump investigations have been conducted when bed scour is present (Balachandar et al, 2000;Kells et al, 2001). Rather, most hydraulic jump experiments have been conducted in channels comprised of prismatic geometry such as staircase bed steps (Chanson, 1994;Chanson and Toombes, 2004) or ogeeshaped dam spillways that impinge upon a horizontal apron (Peterka, 1983).…”
Section: Form Variations Between Natural Jumps and Engineered Jumpsmentioning
confidence: 99%
“…Balachandar and Kells [32] [33], Balachandaret et al [34], Kells et al [35], Lim and Yu [36], Sarkar and Dey [37], Goel and Verma [38] and Dey and Sarkar [39] have studied development of scour holes downstream of an apron for a submerged jet. Downstream scour was studied by many investigators, and a comprehensive state-of-the-art review on the investigations done on scour due to jets was given by Sarkar and Dey [40].…”
Section: Introductionmentioning
confidence: 99%